Regulation of Workers Rights and Obligations in Labor Law - Khairunnisa Siregar; Alya Aisya (AT-TAFAHUM: Journal of Law, 2023)
This study examines the provisions regarding workers' rights and obligations as stipulated in the Manpower Law as a basis for establishing fair and balanced employment relationships. This research is motivated by various employment practices that are detrimental to workers, including inappropriate wage payments, excessive working hours, and suboptimal social security coverage. This situation emphasizes the importance of understanding legal provisions that regulate the proportional status of workers and employers. The purpose of this study is to analyze the forms of regulation of workers' rights and obligations in legislation and their impact on legal certainty in employment relationships. The method used is normative legal research with a legislative and conceptual approach, conducted through a literature review of primary, secondary, and tertiary legal materials. The research stages include collecting legal materials, categorizing legal norms, and systematic analysis of relevant provisions. The results show that the Manpower Law has regulated various workers' rights, such as the right to a decent wage, regulation of working hours and rest periods, protection of occupational safety and health, and employment social security. In addition, workers are also obligated to perform their work in accordance with their employment agreement, comply with company regulations, and maintain a professional attitude in the work environment. These regulations are expected to foster harmonious working relationships, prevent industrial disputes, and enhance legal protection for both workers and employers.